A new species and a new record of Dicuspiditermes Krishna (Blattodea: Isoptera: Termitidae) from the Kerala part of Western Ghats, India. (2nd October 2021) - Amina, Poovoli; Rajmohana, Keloth; Aliyas, Shilimol C.
ABSTRACT: A new species, Dicuspiditermes leghugathrae Amina and Rajmohana sp.nov . (Termitidae) is described and illustrated based on the morphological characters of soldiers and workers. Dicuspiditermes hutsoni (Kemner), a termite species hitherto endemic to Sri Lanka, is reported for the first time from India. Both the species are recorded from the Kerala part of Western Ghats. An identification key to the species of Dicuspiditermes found in India (based on soldier caste), along with a species distribution map is also provided. http://www.zoobank.org/urn:lsid:zoobank.org:act:44AB093B-6A02-4A35-BC1B-3277259A3104